Impact of radiofrequency disinfestation on Tribolium castaneum (Herbst) in wheat flour and its influence on the functional characteristics of wheat flour. Issue 10 (6th August 2021) - Indumathi, C.; Manoj, D.; Loganathan, M.; Shanmugasundaram, S.
Abstract: Wheat flour is the foremost needed food product, but it is vital to prevent infestation. In this study, radiofrequency (RF) heating is suggested as an advanced technology for Tribolium castaneum (Herbst) disinfestation in the flour of wheat. The 100% mortality of all life phases of T. castaneum was noted at 0.9 A of RF current load at 0.5 kV with 15 min exposure time. The susceptibility of T. castaneum to RF heating was eggs>pupae>larvae>adults. Fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC) studies confirmed no detrimental effect in RF‐treated wheat flour. The structural property was elucidated by scanning electron microscopy ( SEM ) analysis. Sensory parameters of chapati made from RF‐treated wheat flour has not been found to be significantly impaired ( p  < .05) with the RF‐untreated wheat flour chapati. RF heating can therefore be proposed as an alternative to pesticide disinfestation technique. Novelty impact statement: Prevention of infestation in wheat flour is a massive issue during storage. Results in this study revealed that radiofrequency heating can be used as an effective disinfestation method for wheat flour without depletion in quality and functional properties. No chemical residues are also considered to be a significant benefit by this approach.